Discovery of Plasmodium vivax N-Myristoyltransferase Inhibitors: Screening, Synthesis, and Structural Characterization of their Binding Mode - Goncalves,V; Brannigan,JA; Whalley,D; Ansell,KH; Saxty,B; Holder,AA; Wilkinson,AJ; Tate,EW; Leatherbarrow,RJ (Journal of Medicinal Chemistry, 2012)
N-Myristoyltransferase (NMT) is a prospective drug target against parasitic protozoa. Herein we report the successful discovery of a series of Plasmodium vivax NMT inhibitors by high-throughput screening. A high-resolution crystal structure of the hit compound in complex with NMT was obtained, allowing understanding of its novel binding mode. A set of analogues was designed and tested to define the chemical groups relevant for activity and selectivity.